KEWENANGAN DPRD KOTA BEKASI MELAKSANAKAN FUNGSI PENGAWASAN TERHADAP PENGELOLAAN APBD KOTA BEKASI - Bimo Aryo Alvi Syahrin; Wiratno, Wiratno (Faculty of Law, Universitas Trisakti, 2023)
The DPRD's ability to manage and balance administrative authority is reflected in three functions: legislation, budgeting and supervision, as stipulated in Law Number 23 of 2014 concerning Regional Government. The problem is whether the implementation of the authority of the Bekasi City DPRD in carrying out the supervisory function of the management of the APBD in Bekasi City for 2020-2021 is in accordance with Law No. 23 of 2014 and what are the obstacles faced by the Bekasi City DPRD in carrying out the supervisory function of APBD management and DPRD efforts to overcome these obstacles. The research uses normative methods. The nature of this research is descriptive analytical, qualitative way. The results of this research and discussion refer to Law Number 23 of 2014 concerning Regional Government by describing the supervisory function of the Bekasi City DPRD on APBD management. Based on interviews and government agency performance reports, the DPRD has carried out a supervisory function in accordance with article 154 of law number 23 of 2014 concerning Regional Government. The conclusion of the study is that the Bekasi City DPRD still has to improve its performance by continuing to update the program in carrying out the oversight function.